An Archaeology of Nkonya Wurupong and Its German Encounters, Volta Region, Ghana. - Owusu-Ansah, D. (University of Ghana, 2018)
This research revolved around the study of the precolonial and colonial cultural lifeways of the people of Nkonya Wurupong. This archaeological investigation was carried out to assess the impact of the 19th and 20th centuries cultural contacts and interactions among the Nkonya people and with other local groups of people (especially the Akan imperial forces) and the colonial authoritative force (Germans) in Nkonya Wurupong, Volta Region of Ghana. An eclectic approach was employed in this study in an attempt to understand and interpret the nature of these encounters and interactions among the various groups of people at Nkonya Wurupong. The eclectic approach included information gathered through a review of archival and documentary sources, ethnographic research, reconnaissance survey as well as archaeological excavations. The study revealed that the interactions between Nkonya Wurupong and the Akan imperial groups led to the usage of some Akan cultural traits in the Wurupong community. The study also revealed that the contacts between the indigenes of Wurupong and the German colonial administrators at Nkonya Wurupong brought about transformations in their education, healthcare services, religion and farming systems. The study has unearthed and provided insights into how the presence of the German colonials in Wurupong relegated the authority of the traditional set-up. The vestiges of the German colonial past in the area serve as shared heritage resources that buttress the presence of the Germans in the Wurupong community. Recommendations were also made on how best to develop the heritage resources of Nkonya Wurupong into tourist attractions.
MPhil.
Keywords: Archaeology; Nkonya Wurupong; Volta Region; Ghana